2020
DOI: 10.1021/acs.jpcb.0c05759
|View full text |Cite
|
Sign up to set email alerts
|

Bulk and Interfacial Properties of the Decane + Water System in the Presence of Methane, Carbon Dioxide, and Their Mixture

Abstract: Molecular dynamics simulations are carried out to study the two-phase behavior of the n-decane+water system in the presence of methane, carbon dioxide, and their mixture at reservoir conditions. The simulation studies were complemented by theoretical modeling using the perturbed-chain statistical associating fluid theory (PC-SAFT) equation of state (EoS) and density gradient theory. Our results show that the presence of methane and carbon dioxide decreases the interfacial tension (IFT) of the decane+water syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
136
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(163 citation statements)
references
References 87 publications
27
136
0
Order By: Relevance
“…The system sizes used here ensure that the finite-size effects are negligible. 38,[40][41][42][43][72][73][74] Each system was equilibrated for 5 ns in the NPT ensemble (only L z varied) and we ran a 5 ns production under NVE conditions. The temperature was controlled using the Nose ´-Hoover thermostat and pressure using the Parrinello-Rahman barostat.…”
Section: Simulation Detailsmentioning
confidence: 99%
See 4 more Smart Citations
“…The system sizes used here ensure that the finite-size effects are negligible. 38,[40][41][42][43][72][73][74] Each system was equilibrated for 5 ns in the NPT ensemble (only L z varied) and we ran a 5 ns production under NVE conditions. The temperature was controlled using the Nose ´-Hoover thermostat and pressure using the Parrinello-Rahman barostat.…”
Section: Simulation Detailsmentioning
confidence: 99%
“…Experiments, [25][26][27][28][29][30][31][32][33][34][35][36][37] theory, [32][33][34][36][37][38][39] and simulations [38][39][40][41][42][43][44][45] have been successfully employed to understand the bulk and interfacial properties of alkane + water + CH 4 /CO 2 systems. These studies have reported the occurrence of, for example, a two-phase region at high pressures.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations